Translation and cultural adaptation of a measure of wisdom assessment: the 3D-WS-19 - Gonçalves, Raquel (2017)
ABSTRACT: Based on the commitment of the Social Gerontology to try to explain the interindividual differences that amplify with the increase of age and to improve the gerontological understanding and intervention, the present study assumed the goal of evaluate the psychometric qualities of the Three Dimensional Wisdom Scale (3D- WS; Ardelt, 2003) as a measure of evaluation of the characteristics associated with wisdom. The results suggest a new factorial solution, the 3D-WS-19, which presents itself as a valid, reliable and suitable instrument for the Portuguese adult population.Keywords: Wisdom; Validation; Confirmatory factor analysis.